SSA challenge program: Lake kivu pilot learning site : Highlights, updates, observations and comments on the ended reviews - Nyamwaro, Sospeter S.; Buruchara, Robin Arani (International Center for Tropical Agriculture, 2010)
Highlights, Updates, Observations and Comments on the Ended Reviews Presented at the Cross-Site Regional Review & Writeshop Meeting of LKPLS, November 08-12, 2010, Kigali, Rwanda